An Appraisal of the Role of Previously Reported Risk Factors in the Age at Menopause Using Mendelian Randomization - Xiaohong Ding; Xiaohong Ding; Rong Tang; Rong Tang; Jinjin Zhu; Jinjin Zhu; Minzhi He; Minzhi He; Huasong Huang; Huasong Huang; Zhenlang Lin; Jianghu Zhu; et al. (Frontiers in Genetics, 2020)
ObjectiveMenopause at a young age is associated with many health problems in women, including osteoporosis, depressive symptoms, coronary disease, and stroke. Many traditional observational studies have reported some potential risk factors for early menopause but have drawn different conclusions. This inconsistency can be attributed mainly to unmodified confounding factors. Identifying the factors causally associated with age at menopause is important for early intervention in women with abnormal menopause timing, and for improving the quality of life for postmenopausal women. This study aims to appraise whether the previously reported risk factors are causally associated with early age at natural menopause (ANM) susceptibility.MethodsWe used Mendelian randomization, a statistical method wherein genetic variants are used to determine whether an observational association between a risk factor and an outcome is consistent with a causal effect.ResultsWomen with earlier age at menarche (β = 0.34, se = 0.16, p = 0.035), lower education level (β = 1.19, se = 0.41, p = 0.004) and higher body mass index (β = −0.05, se = 0.02, p = 0.027) had greater risk for early ANM. The causal link between early age at menarche and early ANM was replicated using ReproGen consortium data (β = 0.23, se = 0.07, p = 0.001). However, a current smoking habit, one of previously reported risk factors, was less likely to be correlated causally with early ANM, suggesting that previous observational studies may not have sufficiently adjusted for confounders.ConclusionOur results help to identify the risk factors of ANM via a genetics approach and future research into the biological mechanism could further help with targeted prevention for early menopause.